2022
DOI: 10.3390/en15124232
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Soiling and Frequency of Optimal Cleaning of PV Panels in Palestine

Abstract: The performance of photovoltaic (PV) solar panels is dependent on certain factors, such as dust effects. Even though Palestine’s energy issues are well-known, no research has been undertaken on the soiling effect on solar energy generation in Palestine’s climatic circumstances. The study’s findings can aid Palestine’s efforts to achieve long-term energy sustainability and solar energy use. Outdoor research was conducted in Tulkarm, Palestine, to explore the impact of dust on PV systems. The current study exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 91 publications
0
1
0
Order By: Relevance
“…In the end, it has been demonstrated by two sites located in the Algerian Sahara that it could be profitable to clean PV panels twice per year, at a cost of $15843 per MW, if the level of soiling exceeds 7% [240,246]. An assessment conducted in Jordan revealed that the average per-day cost of cleaning PV panels is approximately $0.212 per kWp [217,247]. According to research conducted by [237], different methods and tools for cleaning without water were tested in desert climates.…”
Section: Economic Evaluationmentioning
confidence: 99%
“…In the end, it has been demonstrated by two sites located in the Algerian Sahara that it could be profitable to clean PV panels twice per year, at a cost of $15843 per MW, if the level of soiling exceeds 7% [240,246]. An assessment conducted in Jordan revealed that the average per-day cost of cleaning PV panels is approximately $0.212 per kWp [217,247]. According to research conducted by [237], different methods and tools for cleaning without water were tested in desert climates.…”
Section: Economic Evaluationmentioning
confidence: 99%
“…The study revealed that the system performance increased by up to 12% after cleaning, with a cleaning frequency of three times per month. The study conducted by [15] investigated the impact of soiling on the power generation of an 85 kW solar plant in Tulkarm, Palestine. The effect of different cleaning periods on the system's efficiency was analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Abdallah et al (2022) investigated the effects of soiling and the frequency of optimal cleaning of PV panels in Palestine Al-Omary et al (2021). developed a hybrid moving average algorithm for predicting energy in solarpowered wireless sensor nodes Muhaidat et al (2021).…”
mentioning
confidence: 99%